2006
DOI: 10.1103/physrevlett.97.193203
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Quantum Scattering in Strongly Confined Systems

Abstract: We demonstrate that scattering of particles strongly interacting in three dimensions (3D) can be suppressed at low energies in a quasi-one dimensional (1D) confinement. The underlying mechanism is the interference of the s-and p-wave scattering contributions with large s-and p-wave 3D scattering lengths being a necessary prerequisite. This low-dimensional quantum scattering effect might be useful in "interacting" quasi-1D ultracold atomic gases, guided atom interferometry and impurity scattering in strongly co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 34 publications
4
103
0
Order By: Relevance
“…Moreover, the condition (5) defining the appearance of CIR does not have any reliance on the atomic mass. In a series of works [42,43,49], the condition (5) was confirmed by numerically computing the poles of the coupling constant g 1D (k, a ⊥ /a 3D ) at k → 0. Interestingly, it was recently shown that Eq.…”
Section: Atom-atom Confinement-induced Resonancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the condition (5) defining the appearance of CIR does not have any reliance on the atomic mass. In a series of works [42,43,49], the condition (5) was confirmed by numerically computing the poles of the coupling constant g 1D (k, a ⊥ /a 3D ) at k → 0. Interestingly, it was recently shown that Eq.…”
Section: Atom-atom Confinement-induced Resonancesmentioning
confidence: 99%
“…Note that in this limit we have [42,43,49], that is, we have total reflection of the colliding particles. Moreover, the condition (5) defining the appearance of CIR does not have any reliance on the atomic mass.…”
Section: Atom-atom Confinement-induced Resonancesmentioning
confidence: 99%
“…In addition, we study the energy dependence of the corresponding CIRs and observe that all the CIRs can occur even when the two-body potential cannot sustain a weakly bound or quasi-bound state. Moreover, for the energy dependent d-and f -wave CIRs we observe the bosonic and fermionic counterpart of the dual CIR [17], i.e. total transparency (T = 1), which occurs due to the destructive interference of s − d and p − f wave scattering, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore this feature of CIR corresponds to the bosonic and fermionic dual CIR which has been discussed in Ref. [17] for distinguishable particles. Figures 7, 8 and 9 present a convenient visualization of the energy dependence of the transmission extrema for s-, p-, d-and f -wave (dual) CIRs.…”
Section: D-and F -Wave Energy Dependent Cirsmentioning
confidence: 99%
See 1 more Smart Citation